Responsibility as a social capital phenomenon in the eyes of young people. International perspective - Krzywosz-Rynkiewicz, Beata (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryIn this article, we analyse the phenomenon of responsibility and its understanding among young people from Visegrad countries (Poland, Czech Republic, Slovakia, and Hungary). Using the AGA research method, 400 students of the last stages of economic faculties in capital and local universities were examined. The results indicate a personal rather than a social dimension of responsibility. We also found some patterns to depend on the country. Young Poles’ responsibility is more related to the subjective dimension, Hungarians’ to social, Czechs’ to affective, and Slovaks’ to moral one.Key words: responsibility, young people, social capital.